2012
DOI: 10.1111/j.1523-5378.2012.00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Age as Risk Factor for Helicobacter pylori Recurrence in Children in Vietnam

Abstract: The main risk factor for recurrence with H. pylori was found to be age, with the youngest children running the greatest risk. The finding lends support to the observation that early childhood may be the main age of acquisition of H. pylori infection and for postponing attempts of eradication in high-prevalence areas unless motivated for medical reasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Only 2 of 46 children older than 5 years became reinfected compared with 4 of 6 children younger than 5 years. In their recent study on the risks for H pylori recurrence, Nguyen et al 32 found that young age was the most prominent independent risk factor for H pylori recurrence: adjusted hazard ratio among children aged 3 to 4, 5 to 6, and 7 to 8 years, relative to those aged 9 to 15 years, were, respectively, 14.3 (95% CI = 3.8-53.7), 5.4 (95% CI = 1.8-16.3), and 2.6 (95% CI = 0.7-10.4). The young age risk factor for reinfection was not found in the study by Feydt-Schmidt et al 33 Our study results showed a trend for better success rates in older age; nevertheless, this has not reached a statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Only 2 of 46 children older than 5 years became reinfected compared with 4 of 6 children younger than 5 years. In their recent study on the risks for H pylori recurrence, Nguyen et al 32 found that young age was the most prominent independent risk factor for H pylori recurrence: adjusted hazard ratio among children aged 3 to 4, 5 to 6, and 7 to 8 years, relative to those aged 9 to 15 years, were, respectively, 14.3 (95% CI = 3.8-53.7), 5.4 (95% CI = 1.8-16.3), and 2.6 (95% CI = 0.7-10.4). The young age risk factor for reinfection was not found in the study by Feydt-Schmidt et al 33 Our study results showed a trend for better success rates in older age; nevertheless, this has not reached a statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Proton pump inhibitor use on a regular basis can potentially alter the outcome of an H. pylori test. Additionally, lack of interest in eliminating H. pylori and an increase in the infection's resistance to eradication due to old age are two additional potential explanations 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence rates are known to be high in young children or adults with intellectual disability in some previous studies. [353637] This may represent the importance of compliance in terms of maintaining successful eradication status. Lastly, elderly people tend to lack the idea of hygiene and maintain traditional eating habits in Korea.…”
Section: Discussionmentioning
confidence: 99%